Gifts for the gods : images from Egyptian temples - Hill, Marsha, 1949- (The Metropolitan Museum of Art ; Yale University Press, 2007)
Throughout their long history, the ancient Egyptians crafted exquisite statues of bronze, copper, silver and gold as offerings to their gods and for use in temples and shrines. This title focuses on the art and significance of Egyptian metal statuary, presenting insights and up-to-date information on this precious work.